Łowcy odsłon. O blogosferze literackiej słów kilka - Nęcka, Agnieszka (Tematy i Konteksty, 2018)
It’s a paradox that we trust more and more hundreds of anonymous people than people we know and who know our taste. In addition, the number of stars and the scoring of different products is more important than the opinion of a specialist. The author tries to investigate the relationship between “professional” literary criticism and “amateur” blogs on literature. With the advent of e-literature the question on the condition of literary criticism should be reformulated. The author examines the sources of change, takes into account the specificity of writing literary blogs, the relationship between bloggers and publishing market.